2023
DOI: 10.2196/40057
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Social Media and Digital Technologies in COVID-19 Vaccination: Scoping Review

Abstract: Background Social media and digital technologies have played essential roles in disseminating information and promoting vaccination during the COVID-19 pandemic. There is a need to summarize the applications and analytical techniques of social media and digital technologies in monitoring vaccine attitudes and administering COVID-19 vaccines. Objective We aimed to synthesize the global evidence on the applications of social media and digital technologies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 243 publications
(414 reference statements)
0
7
0
Order By: Relevance
“…Given the substantial relevance of digital technologies-based media in the time of COVID-19 pandemic [ 56 ], this study showed a significant relationship between seeking information from social live streaming services and online news media and individuals’ preventive behaviors [ 22 , 41 ]. However, differing from previous studies [ 21 24 ], this study found that social media was not significantly associated with individuals’ preventive behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Given the substantial relevance of digital technologies-based media in the time of COVID-19 pandemic [ 56 ], this study showed a significant relationship between seeking information from social live streaming services and online news media and individuals’ preventive behaviors [ 22 , 41 ]. However, differing from previous studies [ 21 24 ], this study found that social media was not significantly associated with individuals’ preventive behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…It may also stem from gaps between the general population and Twitter users. Vocal antivaccine groups on Twitter might have formed a tight-knit circle, continuously congregating and reinforcing their messages, which could be a significant factor in the perceived decline in vaccine acceptance observed in our data set [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the pandemic, social media was a key source of information on COVID-19 and its vaccines. However, misinformation pertaining to COVID-19 vaccines is prevalent in social media, and it can increase the risk of vaccine hesitancy [ 38 , 39 , 40 ]. Thus, helping parents avoid being deceived by false messages from acquaintances on social media is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…Another study discovered that among Polish parents, the media (e.g., the Internet and television) were the main sources of information on pediatric COVID-19 vaccines [ 36 ]. However, misinformation regarding COVID-19 vaccines is prevalent [ 37 ], especially on social media [ 38 , 39 , 40 ]. The spread of misinformation on COVID-19 vaccines, such as that pertaining to the development and safety of these vaccines, on social media results in hesitancy [ 38 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation